Kinematic Analyses of a Parallel-type Independently Controllable Transmission (International Journal of Automation and Smart Technology, 2011)
This study proposes a novel design of a parallel-type Independently Controllable Transmission (ICT). The parallel-type ICT can produce a continuously variable transmission ratio and a required angular output velocity that can be independently manipulated by a controller yet not affected by the angular velocity of the input shaft. The proposed parallel-type ICT is composed of two planetary gear trains and two transmission-connecting members. A prototype was built to investigate its kinematic characteristics and verify application feasibility.